First-order analyses on the role of surface wind in the long-term contraction of the Indo-Pacific warm pool - Andreas Siswandi; Yudha Setiawan Djamil; Rima Rachmayani; Sri Yudawati Cahyarini; Marfasran Hendrizan (Indonesian Journal of Geography, 2022)
Due to its high evaporation rate, the Indo-Pacific Warm Pool (IPWP) is one of the most important drivers of Indonesian weather and climate. Previous studies, based on the Sea Surface Temperature (SST) proxy records, suggest that IPWP in the mid-Holocene era (~6000 years ago) underwent a contraction (colder on its east-west perimeter and warmer on its center) compared to today’s condition. In this research, the role of surface wind in contracting the IPWP was analyzed by checking the coherency between changes in SST, wind-stress magnitude, and evaporation. The Climate Community System Model version 4 (CCSM4) simulated these three physical quantities under the pre-Industrial and mid-Holocene scenarios. In these simulations, an anti-phase relation between SST and wind-stress magnitude indicates an important role for a weaker surface wind in warming the SST in the center of the IPWP (South China Sea and Banda Sea), mainly during boreal autumn. However, a weaker surface wind did not seem to have simultaneously suppressed ocean evaporation to warm the SST, as shown by the phase-lag relation in their monthly climatology. On the other hand, colder SSTs on the east-west perimeter of the IPWP (western coast of Sumatra and northern coast of Papua) are unlikely to be associated with changes in the surface wind following a weak correlation between their SST and wind-stress magnitude